A COMPARATIVE STUDY BETWEEN STUDENT'S ENGLISH LEARNING ACHIEVEMENT BEFORE AND DURING PANDEMIC TO EIGHT GRADE AT SMPN 13. - Pratiwi, Anggraini Dwi; arjulayana, Arjulayana -; Mulyanah, Euis Yanah (Globish: An English-Indonesian Journal for English, Education, and Culture, 2022)
The research was conducted to determine student learning achievement before the pandemic using face-to-face learning and after pandemic using E-learning. The research was conducted at SMPN 13 Tangerang. In the research, the researcher used a qualitative approach. The researcher took the sample of this study were 10 students of class VIII and 2 English teachers. The instrument in the study was a questionnaire given to students, then observations and interviews with students and teachers. Based on the results of interviews with class VIII students and teachers, it was found that students are more comfortable, and more able to understand and follow the lesson by using the face to face learning model because students can meet face to face, discuss the material given or ask the teacher directly if there is something they haven't. understanding of English material. Likewise, teachers in making materials, managing classes, evaluating students more easily during face-to-face learning. This research proves that student learning achievement is maximized and run well using the face-to-face learning model.Keywords: Learning achievement, Before and during pandemic